PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA PUNCAK PATO DI KANAGARIAN BATUBULEK - Novia Safitri; Indrawati ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study examines community involvement in the development of Puncak Pato Tourism Object in Kanagarian Batubulek, North Lintau Buo District. With the rapid development of the tourism sektor now, governments in each region are competing to develop their regional tourism potential, which aims to increase the attractiveness and standard of living of local communities, which to achieve this requires community participation in the implementation of the development. The data analysis in this study is using descriptive quantitative methods, which involve community involvement in the development of tourism objects which will then be analyzed using the participation theory of Cohen and Upnoff which divides participation into four stages including the decision-making stage, the implementation stage, the stage of enjoying the results. and the evaluation or monitoring stage. The formulation of the problem in this research (1) How is community involvement in the development of Puncak Pato Tourism Object? (2) What is the impact of the development of Puncak Pato Tourism Object on the socio-economic life of the Jorong Pato community?. Data collection techniques in this study were in the form of observation, questionnaires and documentation. The population and samples using the Slovin technique from 227 populations obtained 69 samples and the results of the findings in the field we can see that community involvement in the development of Puncak Pato tourism objects at the decision-making, implementation, enjoying the results and evaluation stages is in the medium category. While the impact of the development of Puncak Pato Tourism Object on socio-economic life as seen from social relations, lifestyle, income, business and work opportunities as well as the reduction in the unemployment rate has not undergone significant changes, this is evidenced by only a small part of the Jorong Pato community receiving changes from the development of the tourist attraction. Keywords: Participation, Impact, Tourism Object Development